2021
DOI: 10.3748/wjg.v27.i29.4913
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end product: A potential biomarker for risk stratification of non-alcoholic fatty liver disease in ELSA-Brasil study

Abstract: BACKGROUND Liver diseases are associated with the excess formation of advanced glycation end products (AGEs), which induce tissue inflammation and oxidative damage. However, the trend of oxidative marker levels according to the steatosis grade in non-alcoholic fatty liver disease (NAFLD) is unclear. AIM To compare serum AGE levels between participants with NAFLD accordingly to steatosis severity in the baseline ELSA-Brasil population. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
4
7
0
Order By: Relevance
“…Whereafter AGEs can participate in the oxidative stress and inflammation of NAFLD by combining with the AGEs receptor (RAGE) to promote the occurrence of hepatic steatosis (hepatocyte steatosis) and even fibrosis and form a positive feedback loop (Table II) (125,126). This is consistent with the study by Pereira et al (127) that AGEs can monitor the progression of mild, moderate and severe NAFLD according to the grade of steatosis (127). Therefore, as aforementioned, in addition to HNA1 and HNA2, AGEs may also promote systemic inflammation in liver disease.…”
Section: Alcoholic Hepatitis (Ah)supporting
confidence: 88%
“…Whereafter AGEs can participate in the oxidative stress and inflammation of NAFLD by combining with the AGEs receptor (RAGE) to promote the occurrence of hepatic steatosis (hepatocyte steatosis) and even fibrosis and form a positive feedback loop (Table II) (125,126). This is consistent with the study by Pereira et al (127) that AGEs can monitor the progression of mild, moderate and severe NAFLD according to the grade of steatosis (127). Therefore, as aforementioned, in addition to HNA1 and HNA2, AGEs may also promote systemic inflammation in liver disease.…”
Section: Alcoholic Hepatitis (Ah)supporting
confidence: 88%
“…Through the multiligand receptor for advanced glycation end products (RAGE) on the vascular cells, AGEs play a key role in the inflammatory process [ 13 ]. It is well established that higher levels of AGEs are linked to diseases such as diabetes, chronic kidney disease, nonalcoholic fatty liver disease, obesity and cardiovascular diseases [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyogo et al [ 43 ] reported that serum levels of AGEs increased in patients diagnosed with NASH compared to healthy controls. Also, it has been reported that steatosis caused by NAFLD was associated with serum AGEs levels in a positive manner [ 44 ]. Also, a case-control study demonstrated that AGEs and their receptor (RAGE) are culprits in liver damage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%